The Consumption Function: A Review Article - Hagen, Everett E. (The Review of Economics and Statistics, 1955)
IT all began when that Schumpeterian innovator, John Maynard Keynes, introduced into a model the idea that savings and investment are brought to equality not (merely) by changes in the rate of interest but by changes in the level of income. Business cycle theorists -some of them -had assumed for decades that fluctuations in the rate of capital formation caused fluctuations in the level of income. But because the then foundations of economic theory included the axiom that the flow of saving and that of investment are brought to equality by the interest mechanism, without aid from change in the income level, cycle theorists were inhibited from pursuing the implications of their assumption, and schizophrenia divided cycle theory from the central body of economic theory. So it was not until Keynes broke the cake of custom and elevated the determinants of saving to a new importance that the search for knowledge of those determinants began. In a limited sense this statement is incorrect, for studies of the relationship between family income and components of family expenditure go back a century. But these were not directed toward an understanding of the determinants of aggregate consumer expenditure in an economy, and so at least in purpose they are not forerunners of the studies discussed here. Not many topics in the history of the development of economic theory have occasioned more discussion within a period of some two decades than has the form of the consumption function since the publication of the General Theory in I936. The discussion continues, among other places, in many of the papers in Savings in the Modern Economy,* the point of departure for this essay. And the end is not yet. On the contrary, the present state of the discussion invites further research. This is natural. The maturation period of an idea is often longer than that of a man.